2020
DOI: 10.3389/fmicb.2020.01216
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth-Promoting Bacteria: Biological Tools for the Mitigation of Salinity Stress in Plants

Abstract: Salinity stress is one of the major abiotic stresses threatening sustainable crop production worldwide. The extent of salinity affected area is expected to cover about 50% of total agricultural land by 2050. Salinity stress produces various detrimental effects on plants’ physiological, biochemical, and molecular features and reduces productivity. The poor plant growth under salinity stress is due to reduced nutrient mobilization, hormonal imbalance, and formation of reactive oxygen species (ROS), ionic toxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
273
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 373 publications
(278 citation statements)
references
References 123 publications
3
273
0
2
Order By: Relevance
“…Hence, the application of beneficial stress-tolerant microbes not only helps in improving the microbial community structure but also in enhancing plant and soil health under salinity. Further research will be required to reveal the hidden mechanisms of stress-tolerant microbial diversity [30]. Moreover, various researchers have demonstrated that the associations between rhizospheric microbes and stressed plants help the plants to adapt to their microenvironment [11].…”
Section: Implication Of Pgpb On Soil Desalinizationmentioning
confidence: 99%
“…Hence, the application of beneficial stress-tolerant microbes not only helps in improving the microbial community structure but also in enhancing plant and soil health under salinity. Further research will be required to reveal the hidden mechanisms of stress-tolerant microbial diversity [30]. Moreover, various researchers have demonstrated that the associations between rhizospheric microbes and stressed plants help the plants to adapt to their microenvironment [11].…”
Section: Implication Of Pgpb On Soil Desalinizationmentioning
confidence: 99%
“…Salinity stress is the major environmental problem all over the world due to which the cultivable land area is decreased, and drastic reduction in root length, biomass, and growth is observed causing a decline in crop yields ( Deinlein et al, 2014 ; Janda et al, 2016 ; Kumar et al, 2020 ). The limitation of plant growth under salinity conditions is primarily due to reduction in photosynthesis rate and high intracellular accumulation of Na + ions, which interfere with various physiological processes ( Assaha et al, 2017 ; Analin et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress-induced accumulation of excess salts is known to affect the function of photosystems by modulating the photosynthetic proteins in chloroplasts causing irreversible damage to the photosynthetic apparatus at all developmental stages in glycophytic plants ( Sun et al, 2016 ; Li et al, 2019 ; Rodríguez-Ortega et al, 2019 ; Zhang et al, 2020 ). Adaptation of plants to salinity stress involves modification of complex physiological traits, metabolic pathways, and gene networks ( Nounjan et al, 2012 ; Gupta and Huang, 2014 ; Ghorbani et al, 2018 ; Kumar et al, 2020 ). The key photosynthetic processes including RuBisCO enzyme activity, ATP generation, electron transport rate (ETR), and efficiency of light capture in the photosystems are seriously affected by salt stress ( Chaves et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress is one of the major abiotic stresses threatening sustainable crop production worldwide. It is estimated that by 2050, world population will reach 9.6 billion and about 50% of agricultural land will be salinity affected [1][2] . Hence, global food productions will need to be increased 57% by 2050 to maintain current level of food supply 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This makes the lands unsuitable for cultivation of crops. Salinity stress produces various detrimental effects on plants physiological, biochemical, and molecular features and reduces productivity 1 .…”
Section: Introductionmentioning
confidence: 99%